Effect of Ta5+ doping on the thermal physical properties of defective fluorite Y3NbO7 ceramics. Issue 2 (28th September 2021) - Song, Dowon; Pyeon, Janghyeok; Ryu, Myeungwoo; Jeon, Hak‐Beom; Oh, Yoon‐Suk; Song, Taeseup; Paik, Ungyu; Yang, SeungCheol; Jung, Yeon‐Gil
Abstract: The effects of substituting the B cation in A3 BO7 ceramics on their thermal physical properties were investigated by applying a large mass difference. Y3 (Nb1‐x Tax )O7 (x = 0, 0.1, 0.2, 0.3, 0.4, and 0.5) ceramics were synthesized, and their structural characteristics were determined. All the fabricated Y3 (Nb1‐x Tax )O7 ceramics showed defective fluorite structures and glass‐like low thermal conductivity (1.18−2.04 W/m∙K at 25°C) because of the highly distorted crystal structure and significant mass difference. Substitution with Ta 5+ enhanced the sintering resistance, leading to superior thermal‐insulating performance via grain boundary scattering. Furthermore, the ceramics exhibited excellent coefficients of thermal expansion, implying the promising applicability of Y3 (Nb1‐x Tax )O7 as new thermal barrier materials. The effect of mass difference on the thermomechanical properties of the ceramics was examined, suggesting a simple strategy for engineering the chemical composition of new thermal barrier materials.